GAYA BAHASA DALAM TEKS SYAIR IKAN TERUBUK - Adawiyah, Robiatul; Mustafa, M Nur; ', Syafrial (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study discusses the language in the Text Style Fish Toli shad ( Syair Ikan Terubuk) poem and discuss the metaphor, personification, hyperbole, litotes and equations in the text poem Toli shad fish. In addition, this study also discusses the meaning is in a style that is found in the text of the poem. This study used a qualitative approach and descriptive method that aims to mendeskripsikangaya any language used in the poem text Toli shad fish. The results of the research is a classification of a style that is found in the poem text Toli shad fish. The results of this study also as a form of documentation style that is present in the poem text Toli shad fish..Keywords: Style Language, Poetry Fish Toli shad